2015
DOI: 10.3109/10715762.2015.1006214
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl cysteine reduces oxidative toxicity, apoptosis, and calcium entry through TRPV1 channels in the neutrophils of patients with polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a common inflammatory and oxidant disease with an uncertain pathogenesis. N-acetyl cysteine (NAC) decreases oxidative stress, intracellular free calcium ion [Ca(2+)]i, and apoptosis levels in human neutrophil. We aimed to investigate the effects of NAC on apoptosis, oxidative stress, and Ca(2+) entry through transient receptor potential vanilloid 1 (TRPV1) and TRP melastatin 2 (TRPM2) channels in neutrophils from patients with PCOS. Neutrophils isolated from PCOS group were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 37 publications
8
47
0
1
Order By: Relevance
“…Evaluation of these compounds in neutrophils showed that the mixed TRPA1/TRPV3/TRPM8 agonists thymol and menthol activated [Ca 2+ ] i flux with EC 50 values in the mid-micromolar range, whereas the other tested monoterpenes were inactive. Furthermore, the TRPV1 agonist capsaicin also stimulated [Ca 2+ ] i flux in human neutrophils (Table 4), which is consistent with previous studies 25 . Together, these results suggest a role of TRP channels in neutrophil responses to essential oil-derived monoterpenes, such as those found in essential oils from Ferula and other plant species.…”
Section: Resultssupporting
confidence: 91%
“…Evaluation of these compounds in neutrophils showed that the mixed TRPA1/TRPV3/TRPM8 agonists thymol and menthol activated [Ca 2+ ] i flux with EC 50 values in the mid-micromolar range, whereas the other tested monoterpenes were inactive. Furthermore, the TRPV1 agonist capsaicin also stimulated [Ca 2+ ] i flux in human neutrophils (Table 4), which is consistent with previous studies 25 . Together, these results suggest a role of TRP channels in neutrophil responses to essential oil-derived monoterpenes, such as those found in essential oils from Ferula and other plant species.…”
Section: Resultssupporting
confidence: 91%
“…In this context, agents that attenuate oxidative stress or associated factors, such as inflammation and energy metabolism impairment, could be important therapeutic targets for both diabetes and MDD. Antioxidant drugs, such as N ‐acetyl‐ l ‐cysteine (NAC) and deferoxamine (DFX), have shown anti‐inflammatory and antioxidant properties by reducing cytokines and oxidative stress, respectively (De Flora et al , 1991; ). Moreover, both NAC and DFX exerted beneficial effects on both diabetes and depression .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that t-BHP treatment increases Ca 2+ release from Ca 2+ stores in endoplasmic and sarcoplasmic reticulum, causing oxidative cell death by targeting mitochondrial permeability and polarization of ΔΨm (Byrne, Lemasters, & Nieminen, 1999;Piret et al, 2004;Zima & Blatter, 2006). Restoration of ΔΨm is crucial for mitochondrial integrity and free radical regulation (Kose & Naziroglu, 2015;Yuruker, Naziroglu, & Senol, 2015). Our results indicated that icaritin was associated with a concentrationdependent maintenance of ΔΨm in t-BHP treated H9c2 cells.…”
Section: Discussionmentioning
confidence: 52%